Protection of animals through criminal law in the light of EU Directive 2024/1203 - Bajović, Vanja (Glasnik Advokatske komore Vojvodine, 2025)
The paper examines the issue of compliance of the criminal legislation of the Republic of Serbia with the EU Directive 2024/1203 on environmental crime. Although the Directive does not deal directly with the protection of animals, several crimes, which the member states insist on implementing, directly relate to the protection of wild animal species. In this regard, the EU member states are required to strictly sanction their killing, destruction, possession, purchase, sale or offering for sale, import or export, as well as the illegal trade in their derivatives. In the criminal law of the Republic of Serbia, these behaviors can be subsumed under various criminal offenses and misdemeanors, the primary goal of which is often not the protection of nature, but the protection of the economy, the market, the customs system, etc. Starting from the thesis that the existing regulation is inadequate to provide animals with adequate protection, the paper analyzes the existing incriminations that provide protection to animals and their compliance with the aforementioned Directive. In particular, we deal with questions that are disputed in theory, such as whether animals can be subject to criminal protection in general, whether they can be granted legal subjectivity, and whether it is adequate to identify them with movable things, that is, "goods". Finally, the issue of the relationship between criminal acts and misdemeanors in this area is discussed, the features of which often overlap and threaten to effectively protect the perpetrator from criminal responsibility by initiating misdemeanor proceedings and imposing a misdemeanor sanction.
Keywords: crimes against wild animals; EU Directive 2024/1203; legal subjectivity; crimes; misdemeanors